Notes on the III CLUP, Latin American Colloquium on Urbanization and Patrimonialization, Guadalajara, Mexico - Queiroz, Pedro Thomé (2023)
The CLUP - Latin American Colloquium on Urbanization and Heritage, is consolidated as a biennial academic event, which brings together researchers from Latin America and the Caribbean, committed to debate and academic productions theoretically and methodologically linked to the contemporary dynamics of urban and rural territories. on the continent, with ways to promote alternative territorial practices. The event is directed by GECIPA (CNPq Research Group on Cities and Heritage in Latin America and the Caribbean), of the Department of Geography of the University of Brasilia/UnB, founded in 2011 and under the general coordination of Professor Everaldo Batista da Coast. The event presented works capable of reflecting and proposing actions on the path towards spatial justice and confronting socio-spatial inequalities in the rural cities of Latin America and the Caribbean. In this sense, we invite scholars of the urbanization and heritage of our continent to participate in the IV CLUP, Bahía Blanca, Argentina, in September 2024. The call or circular has already been published on PatryTer's social networks (Instagram and Facebook) and also on the journal page.